Pengaruh Edukasi Gizi Melalui Akun Instagram Dalam Meningkatkan Pengetahuan Anemia - Syahidah, Amirah; Devriany, Ade; Akhiat, Akhiat (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Adolescent girls are a group that is prone to iron deficiency anemia. Adolescent girls experience an increased need for nutrients, especially iron nutrients. This problem is due to the menstrual cycle that begins to occur in the adolescent phase. In addition, teenagers are starting to pay attention to their body shape, so they go on excessive diets. One of the factors causing this behavior is low knowledge of anemia. Knowledge of anemia can be increased by nutrition education. One method that can be used is education through Instagram. This study aimed to determine the effect of nutrition education through Instagram social media on the anemia knowledge of female students at Poltekkes Kemenkes Pangkalpinang. This research used a pre-experimental design with a one-group pretest-posttest design involving 222 samples selected by stratified random sampling technique. The statistical test used is the Wilcoxon test. The results showed an increase in the average knowledge of the respondents, from a score of 63.96 to 72.64. The statistical test shows an increase in knowledge (p-value 0.000). The level of anemia knowledge of female students was similar between departments. Education through Instagram accounts affects female students' knowledge of anemia at Poltekkes Kemenkes Pangkalpinang. Further researchers may research adolescents in the early years (12-15 years) to be the subject of the following study.